Analyse des Einflusses des Flugverkehrs auf die natürliche Zirrusbewölkung über Europa, Nordamerika und dem Nordatlantik - Krebs, Waldemar (2006)
Air traffic impacts cirrus cloud cover and consequently the radiation budget of the earth. Additionally air traffic may change the optical properties of already existent cirrus clouds and hence the radiation budget of the atmosphere. For the first time the impact of air traffic was investigated over Europe, North-Atlantic and North-Africa for a period of 11 months of 2004 with a high temporal-resolution satellite sensor. A significant correlation between cirrus cloud cover and air traffic density was shown for the region of interest. The air traffic induced cirrus cloud cover has been estimated with 0.6±0.2% for this region. Global extrapolation yields 0.17± 0.06%. Based on this value an air traffic induced radiative forcing of 34 mW m2 follows. The direct investigation of the impact of air traffic on outgoing fluxes yields a warming effect of 1.1 W m2 for the region of interest. This value has been calculated from the difference between outgoing fluxes of air traffic free regions and the whole region. The global extrapolation yields a warming of 290 mW m2 . However this value is very uncertain. Additionally further aspects have been investigated. As a result, a strong dependency of the impact of air traffic on the geographic location and daytime could be shown.